The Brides of Rollrock Island - Lanagan, Margo (New York Alfred A. Knopf, 2012)
On remote Rollrock Island, men go to sea to make their livings--and to catch their wives. The witch Misskaella knows the way of drawing a girl from the heart of a seal, of luring the beauty out of the beast. And for a price a man may buy himself a lovely sea-wife. He may have and hold and keep her. And he will tell himself that he is her master. But from his first look into those wide, questioning, liquid eyes, he will be just as transformed as she. He will be equally ensnared. And the witch will have her true payment.
Keywords: Magic -- Witches -- Selkies